Pengaruh Pengalaman PKL sebagai Sarana Pembentukan Kepercayaan Diri dan Kesiapan Kerja Siswa SMK - Rian Mahesa; Adel Lia Mardiana; Rijal Abdullah; Indah Sartika; Hendra Hidayat (Jurnal Pendidikan Teknik Mesin, 2025)
This study aims to analyze the influence of Field Work Practice (PKL) experience on the formation of self-confidence and work readiness of vocational high school students through a quantitative approach with a survey method using a Likert scale instrument, and the results of statistical analysis show that PKL has a significant influence, especially through aspects of knowledge and skills acquired during industrial practice, while the self-confidence of grade XII students who have carried out industrial work practice (PKL) does not provide a significant contribution, so this study confirms that the effectiveness of PKL as a character builder and work readiness is highly dependent on the quality of the industrial environment, consistent guidance, and the suitability of the program to the needs of the ever-evolving world of work.